Phase field approach based brittle fracture study for a single edge centre-notched specimen under plane stress/strain condition - Khandelwal, N.; Murthy, A. Ramachandra (Journal of Structural Engineering, 2024)
In the last few years, the application of variational approach-based phase field model in fracture mechanics has gained attention for simulating complicated crack behavior. The phase field model does not require the presence of predefined cracks. Crack path in the phase field model for damaged material is tracked by a phase field variable that varies between 0 and 1. This paper aims to carry out fracture analysis of quasi-static brittle specimen under plane stress and plane strain conditions using phase field method. Phase field modelling for two-dimensional quasistatic brittle fracture has been implemented using user-defined subroutines in ABAQUS software. Centre-notched specimen under mode-I and mode-II loading were analysed and the predicted behaviour compared with the literature. The effect of thickness on load carrying capacity of specimens were investigated and it was observed that for similar thickness, load carrying capacity is higher and occurance of fracture delayed in plane stress condition as compare to plane strain case. Other observations from the study include that thickness does not have any effect on the displacement at which sudden fracture occur, in both plane stress and plane strain cases.